2022
DOI: 10.1093/ndt/gfac311
|View full text |Cite
|
Sign up to set email alerts
|

RESET-PKD: a pilot trial on short-term ketogenic interventions in autosomal dominant polycystic kidney disease

Abstract: Background Ketogenic dietary interventions (KDI) have been shown to be effective in animal models of polycystic kidney disease, but data from clinical trials are lacking. Methods Ten ADPKD patients with rapid disease progression were enrolled at visit V1 and initially maintained a carbohydrate (CHO)-rich diet. At V2, patients entered one of the two KDI arms: a 3-day water fast (WF) or a 14-day ketogenic diet (KD). At V3, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…30 The trial demonstrated feasibility and successful ketogenesis induction. 30 The KETO-ADPKD study investigated 12-week ketogenic diet interventions in patients with ADPKD. 31 The study included three arms: 23 patients with ADPKD on ketogenic diet, 21 patients on water fasting for 3 days every 14 days, and 19 patients on control ad libitum food intake.…”
Section: Clinical Studies and Benefitsmentioning
confidence: 93%
See 1 more Smart Citation
“…30 The trial demonstrated feasibility and successful ketogenesis induction. 30 The KETO-ADPKD study investigated 12-week ketogenic diet interventions in patients with ADPKD. 31 The study included three arms: 23 patients with ADPKD on ketogenic diet, 21 patients on water fasting for 3 days every 14 days, and 19 patients on control ad libitum food intake.…”
Section: Clinical Studies and Benefitsmentioning
confidence: 93%
“…30 There was no specification on the preference of animal or plant source of protein. 30 The KETO-ADPKD study showed potentially favorable short-term outcomes, including decreased cystic liver growth (255 ml/m, P 5 0.01), likely due to glycogen depletion, and an acute improvement in kidney function (ΔeGFR of 15 ml/min, P 5 0.01). 31 The short-term increase in creatinine-based eGFR might be related to decreased animal protein (meat) intake, leading to a decreased creatinine pool size and lowered serum creatinine, 32 rather than true GFR change.…”
Section: Clinical Studies and Benefitsmentioning
confidence: 99%
“…Caution should be applied to the interpretation of this retrospective study since only half of the patients were able to comply with the diet and the side effects reported suggest potential long-term tolerability and safety issues (kidney stones, increased cholesterol) ( Strubl et al, 2021 ). In a follow-up study, Oehm demonstrated the feasibility of a short-term ketogenic intervention in 10 ADPKD patients (RESET-PKD 72h fast or 14 days of a KD) where TLV was decreased while no changes in TKV were observed ( Oehm et al, 2022a ; Oehm et al, 2022b ). Despite the challenges identified, large-scale trials such as the ongoing KETO-ADPKD (NCT04680780) study will address the feasibility and the therapeutic potential of longer-term ketogenesis interventions in ADPKD ( Ong and Torra, 2022 ).…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%
“…The ketogenic diet (KD) is a very low carbohydrate, very high fat diet that drives the body to shift its energy dependence from glucose to ketones. Although the KD was developed in the 1920s as a therapeutic option for children with drug-resistant epilepsy [1], scientific and consumer interest in the KD has markedly increased over the past 2 decades owing to its potential beneficial effects on illnesses including cancer, type 2 diabetes, and polycystic kidney disease as well as its potential as a weight loss strategy [2–5]. However, adherence to a KD may have adverse effects on bone turnover, mineralization, and fracture risk [6 ▪▪ ,7,8 ▪ ].…”
Section: Introductionmentioning
confidence: 99%